High-Density Genetic Variation Map Reveals Key Candidate Loci and Genes Associated With Important Agronomic Traits in Peanut - Zhao, Huiling; Tian, Ruizheng; Xia, Han; Li, Changsheng; Li, Guanghui; Li, Aiqin; Zhang, Xianying; Zhou, Ximeng; Ma, Jing; Huang, Huailing; Zhang, Kun; Thudi, Mahendar; et al. (Frontiers in Genetics, 2022)
Peanut is one of the most important cash crops with high quality oil, high protein content, and many other nutritional elements, and grown globally. Cultivated peanut (Arachis hypogaea L.) is allotetraploid with a narrow genetic base, and its genetics and molecular mechanisms controlling the agronomic traits are poorly understood. Here, we report a comprehensive genome variation map based on the genotyping of a panel of 178 peanut cultivars using Axiom_Arachis2 SNP array, including 163 representative variety of different provinces in China and 15 cultivars from other nine countries. According to principal component analysis (PCA) and phylogenetic analysis, the peanut varieties were divided into seven groups, notable genetic divergences between the different areas were shaped by environment and domestication. Using genome-wide association study (GWAS) analysis, we identified several marker-trait associations (MTAs) and candidate genes potentially involved in regulating several agronomic traits of peanut, including one MTA related with hundred seed weight, one MTA related with total number of branches and 14 MTAs related with pod shap. This study outlines the genetic basis of these peanut cultivars and provides 13,125 polymorphic SNP markers for further distinguishing and utility of these elite cultivars. In addition, the candidate loci and genes provide valuable information for further fine mapping of QTLs and improving the quality and yield of peanut using genomic-assisted breeding method.